Electrodynamics of plasma-filled corrugated coaxial structure - Onischenko, I.N.; Sidorenko, D.Yu.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2000)
The interaction of electronic beam with plasma-filled coaxial waveguide with corrugated external radius is investigated. The dispersion equation, which describes interaction of beam with such slowing down structure, is obtained. The properties of eigen waves of structure depending on plasma density are investigated numerically. It is shown that for non-relativistic electronic beams maximal growth rate of instability for plasma-filled slowing down structure considerably exceeds the one for vacuum structure. The non-linear estimations of waves excitation efficiency in such system are carried out.